2023
DOI: 10.1161/strokeaha.122.039660
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Is Inversely Associated With Severe Intracranial Stenosis in Stroke-Free Participants of NOMAS

Abstract: Background: Although protective in secondary stroke prevention of intracranial arterial stenosis (ICAS), it is uncertain if the benefits of leisure time physical activity (LTPA) extend to asymptomatic ICAS or extracranial carotid stenosis (ECAS). Therefore, we sought to determine LTPA’s relationship with ECAS and ICAS in a stroke-free, race-ethnically diverse cohort. Methods: This cross-sectional study included participants from the magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…67–69 In a recently published cross-sectional study including participants from the MRI of the Northern Manhattan Study, of whom 1274 had leisure time physical activity (LTPA) assessments at enrollment, showed that LTPA was strongly associated with asymptomatic ≥70% intracranial artery stenosis (95% CI, 0.94-0.99. 70 In the Stenting and Aggressive Medical Management for Prevention of Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) trial, patients with 70% to 99% stenosis of intracranial arteries were strictly controlled for risk factors and were divided into medical therapy group and stenting group. The risk factor control strategies in the study included keeping systolic blood pressure <140 mmHg (<130 mmHg if diabetic), maintaining LDL <70 mg/dL and HbA1c <7%, cessation of smoking, losing weight, and physical activity.…”
Section: Nonpharmacological Management Of Icadmentioning
confidence: 99%
See 1 more Smart Citation
“…67–69 In a recently published cross-sectional study including participants from the MRI of the Northern Manhattan Study, of whom 1274 had leisure time physical activity (LTPA) assessments at enrollment, showed that LTPA was strongly associated with asymptomatic ≥70% intracranial artery stenosis (95% CI, 0.94-0.99. 70 In the Stenting and Aggressive Medical Management for Prevention of Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) trial, patients with 70% to 99% stenosis of intracranial arteries were strictly controlled for risk factors and were divided into medical therapy group and stenting group. The risk factor control strategies in the study included keeping systolic blood pressure <140 mmHg (<130 mmHg if diabetic), maintaining LDL <70 mg/dL and HbA1c <7%, cessation of smoking, losing weight, and physical activity.…”
Section: Nonpharmacological Management Of Icadmentioning
confidence: 99%
“…[67][68][69] In a recently published cross-sectional study including participants from the MRI of the Northern Manhattan Study, of whom 1274 had leisure time physical activity (LTPA) assessments at enrollment, showed that LTPA was strongly associated with asymptomatic ≥70% intracranial artery stenosis (95% CI, 0.94-0.99. 70 The results suggested that aggressive medical therapy combined with risk factor management was associated with better outcomes than intracranial stenting. 33,71 Specifically, greater physical activity decreased the likelihood of a recurrent stroke, myocardial infarction, or vascular death.…”
Section: Physical Inactivity Is a Risk Factor For Strokementioning
confidence: 99%
“…The clear association between physical activity and vascular health in a stroke-free population of older people, shown by Yang et al, 2 is highly important. The inactivity level was higher than in most areas of the United States, but Northern Manhattan is an urban area with a city environment.…”
mentioning
confidence: 94%
“…NOMAS 2 is an urban cohort with mixed ethnical background. Forty % of the 1274 included participants were inactive.…”
mentioning
confidence: 99%
See 1 more Smart Citation